A guide to U.S. environmental law - Rowell, Arden; Zeben, Josephine A. W. van, 1984- (University of California Press, 2021)
"[T]his unique primer distills the environmental law and policy of the United States into a practical guide for a nonlegal audience, as well as for lawyers trained in other regions. The first part explains the basics of the American legal system: key actors, types of laws, and overarching legal strategies for environmental management. The second part delves into specific environmental issues (pollution, ecosystem management, and climate change) and how American law addresses each. Chapters include summaries of key concepts, discussion questions, and a glossary of terms, as well as informative 'spotlights'--brief overviews of topics"--